The performance of solvent-based direct air capture across geospatial and temporal climate regimes - Brooks, Bjørn-Gustaf J.; Geissler, Caleb H.; An, Keju; McCoy, Sean T.; Middleton, Richard S.; Ogland-Hand, Jonathan D. (Frontiers in Climate, 2024)
Liquid-solvent direct air capture (DAC) is a prominent approach for carbon dioxide removal but knowing where to site these systems is challenging because it requires considering a multitude of interrelated geospatial factors. Two of the most pressing factors are: 1) how should DAC be powered to provide the greatest net removal of CO2 and 2) how does weather impact its performance? To investigate these questions, this study develops a process-level model of a liquid-solvent DAC system and couples it to a 20-year dataset of temperature and humidity conditions at a ~9km resolution across the contiguous US. We find that the amount of CO2 sequestered could be 30% to 50% greater than the amount of CO2 removed from the atmosphere if natural gas is burned on site to power DAC, but that the optimal way to power DAC is independent of capture rate (i.e., weather), depending solely on the upstream GHG intensity of electricity and natural gas. Regardless of how it is powered, air temperature and humidity conditions can change the performance of DAC by up to ~3x and can also vary substantially across weather years. Across the continuous US, we find that southern states (e.g., Gulf Coast) are preferrable locations for a variety of reasons, including higher and less variable air temperature and relative humidity. Lastly, we also find the performance of liquid-solvent DAC calculated with monthly means is within 2% of the estimated performance calculated with hourly data for more than a third of the country, including in the states with weather most favorable for liquidsolvent DAC.